Perceptions of Recipients of the Family Hope Program (PKH) in Family Capacity Building Meetings (P2K2) to Improve Nutrition for Breastfeeding Mothers and Toddlers in Klemunan Village, Wlingi District, Blitar Regency - Panca Radono; Retno Wulan Anggraini; Nurwijayanti (Universitas STRADA Indonesia, 2022)
PKH's mission is to reduce poverty considering that Indonesia's poor population until March 2016 was still 10.86% (BPS, 2016). PKH is expected to significantly reduce the number of poor people & inequality, in line with the increase in the Human Development Index (IPM). The obligations of PKH participants in the health sector include checking the content of pregnant women, providing nutrition & immunizations, and weighing children under five. This study uses a descriptive qualitative research method after the data is obtained it will be analyzed so that conclusions can be drawn in the study. According to Miles and Huberman (1984) that the activity of analyzing descriptive qualitative data is carried out interactively and lasts to completion. Nutritious food is important for the health and development of children. Balanced nutrition is essential for breastfeeding mothers because it is closely related to milk production and the growth and development of their babies. After following the material on health and the importance of nutrition for breastfeeding mothers and toddlers, there were significant changes made by breastfeeding mothers and their toddlers. According to the informant's information, the informants began to control what should be processed & eaten for nursing mothers and healthy ingredients to be given to their toddlers. Perceptions of Recipients of the Family Hope Program KPM PKH on P2K2 activities carried out by PKH facilitators significantly affect the improvement of nutrition for breastfeeding mothers and toddlers in Kel. Klemunan, Kec. Wlingi, Kab. Blitar. The significant influence made by PKH recipients is starting a movement to pay attention to nutrition given to breastfeeding mothers and toddlers with innovation and creativity with simple conditions.